The Effectiveness of Physiotherapy Exercises in Subacromial Impingement Syndrome: A Systematic Review and Meta-Analysis - Hanratty, Catherine E.; McVeigh, Joseph G.; Kerr, Daniel P.; Basford, Jeffrey R.; Finch, Michael B.; Pendleton, Adrian; Sim, Julius (Seminars in arthritis and rheumatism, 2012)
To evaluate the effectiveness of exercise in the treatment of people with subacromial impingement syndrome (SAIS). A systematic review and meta-analysis were conducted. Ten electronic databases were searched from the dates of their inception until August 2010. Included studies were randomized controlled trials investigating exercise in the management of SAIS. Outcomes were pain, strength, function, and quality of life. Data were summarized qualitatively using a best evidence synthesis. Treatment effect size and variance of individual studies were used to give an overall summary effect and data were converted to standardized mean difference with 95% confidence intervals (standardized mean difference (SMD) (CI)). Sixteen studies were included (n = 1162). There was strong evidence that exercise decreases pain and improves function at short-term follow-up. There was also moderate evidence that exercise results in short-term improvement in mental well-being and a long-term improvement in function for those with SAIS. The most common risk of bias across the studies was inadequately concealed treatment allocation. Six studies in the review were suitable for meta-analysis. Exercise had a small positive effect on strength of the rotator cuff in the short term (SMD −0.46 (−0.76, 0.16); P = 0.003) and a small positive effect on long-term function (SMD −0.31 (−0.57, 0.04); P = 0.02). Physiotherapy exercises are effective in the management of SAIS. However, heterogeneity of the exercise interventions, coupled with poor reporting of exercise protocols, prevented conclusions being drawn about which specific components of the exercise protocols (ie, type, intensity, frequency and duration) are associated with best outcomes.